Connectivity and divergence of symbiotic bacteria of deep-sea hydrothermal vent mussels in relation to the structure and dynamics of mid-ocean ridges - Jang, Sook-Jin; Chung, Yujin; Jun, Siyeong; Won, Yong-Jin (Frontiers in Marine Science, 2022)
The population divergence process of deep-sea vent invertebrates is driven by both biotic (e.g., dispersal during the larval stage) and abiotic factors such as deep-ocean currents, depth, and the geological setting of vents. However, little is known regarding the divergence of hydrothermal vent microorganisms. Therefore, our study sought to investigate the influence of geological and geographic factors on the divergence of symbiotic bacteria of Bathymodiolus vent mussels. The genetic differentiation patterns of symbionts were examined using next-generation sequencing DNA data in two ocean basins with distinct geological features: the slow-spreading Central Indian Ridge (CIR) and the fast- or superfast-spreading eastern Pacific Ridges. Our findings showed that the degree of differentiation of symbiont populations was geographically hierarchical: the highest between ocean basins, followed by inter-ridge sites between the East Pacific Rise and the Pacific Antarctic Ridge. The Easter Microplate intervening these two ridges acted as a biogeographic physical barrier for both symbionts and their host mussels. On a scale of intra-ridge, symbionts showed isolation by distance in the CIR but not in the eastern Pacific ridges. These contrasting genetic patterns relate to different ridge spreading rates determining most of the geological characteristics of mid-ocean ridges that affect the connectivity of vent habitats in space and time. At the intra-ridge geographic scale of the CIR, population divergence processes of both symbionts and hosts from separate three ridge segments were analyzed in detail using a genetic model of isolation with migration (IM). The phylogenetic topology of symbiont populations was congruent with the host populations, indicating the influence of common historical and physical constraints for habitats and dispersal between vents in the Central Indian Ridge. Collectively, our findings provide key insights into the dynamics of microbial population divergence in deep-sea vents.